Riboflavin in Brown-Vialetto-Van Laere Syndrome - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs)
Investigators at Great Ormond Street Hospital, London, UK, and multiple centers internationally report the response to high-dose oral riboflavin therapy in 18 patients from 13 families with mutations in SLC5ZA2, encoding riboflavin transporter RTVT2, a new causative gene for Brown-Vialetto-Van Laere syndrome (BVVLS), a progressive neurodegenerative disorder leading to death in childhood.